Perbedaan Derajat Keparahan Penyakit Berdasarkan Skor Psoriasis Area and Severity Index (PASI) Terhadap Profil Lipid pada Psoriasis Vulgaris - Annisa Marsha Evanti; Fitri Kasmitasari; Muhammad Eko Irawanto (Jurnal Health Sains, 2022)
Psoriasis vulgaris is a chronic systemic autoimmune disease that affects skin, joint, nail and other organ with clinical manifestation well-defined erythematous plaques with thick silvery scales. Psoriasis vulgaris is associated with dyslipidemia include elevated level of total cholesterol, LDL and triglyceride serum and decreased HDL serum levels. Psoriasis Area and Severity Index (PASI) is an examination to assess the severity of psoriasis vulgaris and mostly used in clinical practice and research. Purpose: To determine differences in disease severity based on PASI scores on lipid profiles in psoriasis vulgaris patients. Methods: This research is an observational analytic study with cross sectional research design conducted at Dr. Moewardi General Hospital Surakarta from February to March 2022. The total number of subjects was 25 patients with psoriasis vulgaris. All data were analyzed using SPSS version 21 application (IBM Corp. Chicago, USA). Bivariate analysis with parametric independent T test and Mann-Whitney test were used to determine the differences of total cholesterol, LDL, triglyceride and HDL serum level between PASI <10 and PASI ≥10 with p<0,05 considered significant. Results: Patients with PASI <10 had mean value of total cholesterol levels 187,53±26,39, LDL levels 128,24±28,37, triglyceride levels 115,88±61,74 and HDL levels 46,29±11,98 while in patients with PASI ≥10 had value of total cholesterol levels 218,75±34,92 (p=0,020), LDL levels 145,63±35,76 (p=0,201), triglyceride levels 201,88±158,04 (p=0,215) and HDL levels 44,13±11,36 (p=0,672). There is a significant difference between the severity of the disease based on the PASI score on total serum cholesterol levels in psoriasis vulgaris patients. Conclusion: There was a significant difference between PASI score <10 and PASI score ≥10 on total serum cholesterol levels in patients with psoriasis vulgaris.